Newly developed narrow-band filters for stabilizing load voltage and compensating for voltage unbalance with harmonics in islanded Microgrid. (May 2022) - Elnady, A.; Adam, A.A.; Alshabi, M.
Highlights: Recursive narrow-band filter is developed to estimate the voltage fundamental and harmonics. Recursive narrow-band filter is adopted to estimate the voltage unbalance. The suggested centralized control scheme is proposed to stabilize the voltage at the balanced and unbalanced loads. The suggested centralized control scheme is developed to share the load power among the employed inverters. Abstract: This paper presents an accurate estimation and tracking tool for voltage unbalance and current harmonics in the microgrid. These current harmonics interact with a feeder impedance and yield voltage harmonics at the load bus. The suggested estimation depends on newly formulated recursive digital narrow-band filters (N-B filters). This developed N-B filter is used to estimate the fundamental voltage and current harmonics. Moreover, this paper also introduces the least mean fourth-based adaptive proportional-integral controller (LMF-PI) for a centralized control scheme that improves the dynamic and steady-state performance for voltage and power of the loads. The voltage stability is realized by adjusting positive-sequence voltage around 1 per unit and compensating for all negative-sequence and zero-sequence voltages along with the mitigation of voltage harmonics. The suggested control scheme also enables the inverters to equally share the load power. The effectiveness of the developed estimation tool along with the proposed control scheme is justified by simulation results for a microgrid under different loading conditions with balanced, unbalanced, and nonlinear loads. Graphical abstract: Image, graphical abstract